Two dimensional convolutional neural network CNN approach for detection of Bangla sign language - Nag, Pollock; Khan, Tamim Mahmud; Biplob, Shaikh Mehedi Hasan; Barmon, Rachayita; Rahman, MD. Minhaj (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.